A review of antimicrobial resistance challenges in Nigeria: The need for a one health approach - Emmanuel Dayo Alabi; Akeem Ganiyu Rabiu; Ayodele Timilehin Adesoji (One Health)
The discovery of penicillin and other antibiotics has revolutionized modern medicine. However, overreliance on antibiotics has led to a global antimicrobial resistance (AMR) crisis, jeopardizing progress made over the past decades. Antimicrobial resistance poses a critical public health challenge, affecting humans, animals, and the environment. The AMR challenge is particularly dire in Nigeria owing to the extensive antibiotic use across various sectors and ineffective antimicrobial stewardship programs. This narrative review summarizes the literature from January 2018 to December 2023, focusing on the current trends in AMR in Nigeria, including knowledge of antimicrobial usage, prescription patterns, and adherence to guidelines for humans, animals, and their shared environments. High antibiotic resistance patterns were detected in isolates recovered from healthcare settings, food supply chains, companion animals, wildlife, and the environment. Factors exacerbating the AMR crisis in Nigeria include poor regulation of antimicrobial agents, improper empirical prescriptions, inadequate infection prevention practices, arbitrary and prophylactic use of antibiotics in food-producing animals, environmental contamination, and insufficient surveillance programs. To effectively mitigate this crisis, it is essential to adopt the One Health approach, which prioritizes collaborative efforts among stakeholders, including governmental agencies, healthcare institutions, veterinary experts, farmers, and the scientific community, to address the convergence of human, animal, and environmental health. These efforts will promote transdisciplinary surveillance approaches and the establishment of policies aimed at ameliorating the impact of AMR on the Nigerian economy, the well-being of its population, and diverse ecosystems.